Juridical Review of The Application of Digital Mapping (Plotting) of Land Ownership Rights in The Prevention of Multiple Certificates - Mashendra Mashendra; Deddy Mursanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The implementation of land registration aims to create an accurate information center regarding land ownership. To ensure that land registration administration runs effectively, the Computerization of Land Activities (KKP) policy is implemented gradually and thoroughly. Even so, the application of a computerized system that is so sophisticated, still finds overlapping ownership of land titles. Overlapping the certificate will result in legal uncertainty for the certificate holder, because the main purpose listed is to get the certificate as valid evidence.. Sampling in this study was carried out purposively with a non-random sampling technique that focused only on land that had multiple certificates. The data analysis pattern in this study is based on qualitative methods. The findings of this study are thatThe implementation of Computerization of Land Activities (KKP) at BPN City of Baubau in preventing the occurrence of double certificates is carried out with all processes from the beginning of land registration to issuance of certificates and stored digitally.The factors that result in the occurrence of a double certificate can be seen from 2 (two) things, namely first, when viewed from the factor of the Community. Second, if it is seen from the human resource factor of the Land Officedue to carelessness and carelessness of the land officers.